English Borrowing Words in Jagatplay News Articles - I Gusti Ngurah Galih Pawitra; I Made Suastra; Luh Putu Laksminy (Jurnal Langua, 2023)
Language borrows words from another language when cultural contact occurs. It can’t be denied that borrowing words can be found commonly anywhere, not to mention on the internet. This paper is entitled “English Borrowing Words in JagatPlay News Articles”, aimed to analyze the borrowed words used in the website with the focus of the meaning change. The data of this study is taken randomly from JagatPlay news articles, which is considered to be relevant to the study. The data then analyzed using the theory proposed by Bloomfield (1935), Hockett (1958), and mainly Baugh (1993). After that, it is presented by classifying the word by determining whether they underwent a change in meaning or not and the sociolinguistics aspect of the change. From the analysis, some borrowed words used in the article by its writer undergo a change in meaning, but also there are some words that stick with the original meaning, and may even stick with the spelling. Words like implisit, eksistensi, fenomenal, sporadis era, spiritual, veteran don’t undergo meaning change. Meanwhile, words like ikon, visual, legendaris, konsol, objektif, and drama are considered to be words that have undergone some change in the meaning, typically degeneration. All the same, it can’t be denied that the usage of borrowing words in media, in this case in a news website, is relatively used often.